Simplifying
4w2 + 24w = 0
Reorder the terms:
24w + 4w2 = 0
Solving
24w + 4w2 = 0
Solving for variable 'w'.
Factor out the Greatest Common Factor (GCF), '4w'.
4w(6 + w) = 0
Ignore the factor 4.
Subproblem 1
Set the factor 'w' equal to zero and attempt to solve:
Simplifying
w = 0
Solving
w = 0
Move all terms containing w to the left, all other terms to the right.
Simplifying
w = 0
Subproblem 2
Set the factor '(6 + w)' equal to zero and attempt to solve:
Simplifying
6 + w = 0
Solving
6 + w = 0
Move all terms containing w to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + w = 0 + -6
Combine like terms: 6 + -6 = 0
0 + w = 0 + -6
w = 0 + -6
Combine like terms: 0 + -6 = -6
w = -6
Simplifying
w = -6
Solution
w = {0, -6}